FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN DAMPAKNYA TERHADAP COST OF EQUITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sukma, Fitria; Fitri, Meutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to determine the effect of company size, profitability, leverage, and quality of corporate governance on corporate social responsibility disclosure, as well as to determine the impact of corporate social responsibility disclosure on the cost of equity of the company. The type of research used is quantitative research. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. Sampling was carried out using the purposive sampling method, and produced a sample of 57 companies. The data used in this study are secondary data in the form of financial reports, annual reports, and company sustainability reports from the sample company's website and the Indonesia Stock Exchange website. The analysis technique used is a multiple linear analysis technique. The results showed that the size of the company and the quality of corporate governance have a positive effect on the disclosure of corporate social responsibility. Leverage negatively affects corporate social responsibility disclosure. Meanwhile, profitability does not affect the disclosure of corporate social responsibility. The results also showed that disclosure of corporate social responsibility negatively affects the cost of equity.